In Situ Time‐Dependent and Progressive Oxidation of Reduced State Functionalities at the Nanoscale of Carbon Nanoparticles for Polarity‐Driven Multiscale Near‐Infrared Imaging. Issue 3 (7th February 2018) - Srivastava, Indrajit; Misra, Santosh K.; Tripathi, Indu; Schwartz‐Duval, Aaron; Pan, Dipanjan
Abstract: Surface abundant oxidize‐able functionalities at the nanoscale of carbon dots are prone to undergo sequential aerial oxidation leading to polarity‐driven wavelength tuning of their photoluminescence and consequently boost their quantum yields. With the progression of time, aerial oxidation is gradually increased from 1 to 6 h; consequently, a remarkable shift in the emission peak is observed, likely due to a gradual decrease in their respective band gaps leading to red shift of their photoluminescence. These bands are found to be dependent on the time of hydrothermal treatment of the model small molecules, i.e., benzophenone imine, and not on the size of the carbon core, as is the typical case for semiconductor quantum dots. Due to their high quantum yield (≈31%), it is demonstrated that these wavelength‐tuned carbon nanoparticles can be efficiently used for multiscale bioimaging, i.e., intracellular, deep tissue ex vivo and in vivo fluorescence bioimaging. Abstract : Carbon dots with surface‐abundant oxidizeable functionalities undergo sequential aerial oxidation leading to polarity‐driven wavelength tuning of their photoluminescence. It consequently boosts their quantum yields and improves deep tissue ex vivo and in vivo fluorescence bioimaging abilities.